Laura E. Beer and Jacqueline C. Birnbaum (Eds.): Trauma-Informed Music Therapy: Theory and Practice - Ramos-Watt, Sandra (Voices: A World Forum for Music Therapy, 2023)
This is a book review of Trauma-Informed Music Therapy: Theory and Practice edited by Laura E. Beer and Jacqueline C. Birnbaum and published by Routledge in 2022. The music therapy profession is fortunate to have a timely and comprehensive study of the principles of trauma-informed care, one that tackles challenging issues related to race, culture, systemic oppression, power dynamics, and gender-identity. To practice ethically, it is critical that we understand how and why trauma manifests in our clients’ lives. Because of the prevalence of trauma in the lives of people worldwide, professional music therapists have a moral responsibility to learn about trauma-informed care. Resources that afford health practitioners an opportunity to enhance the clinical skills needed to treat survivors of trauma are essential. Trauma-Informed Music Therapy: Theory and Practice is a vital book that can support music therapists in developing knowledge that can aid in providing effective care to the clients they serve.